Penerapan Model Pembelajaran Problem Based Learning (Pbl) Untuk Meningkatkan Pemahaman Konsep - Hidayat, Muhammad Yusuf; Maulida, Siti Rikha Hanum (Al-Khazini: Jurnal Pendidikan Fisika, 2022)
This study aims to describe students' conceptual understanding before being taught using a problem based learning (PBL) learning model, to describe students' conceptual understanding after being taught using a problem based learning (PBL) learning model, and to analyze the increase in conceptual understanding before and after the application of the model. problem based learning (PBL) at SMAN Wongsorejo. This type of research is pre-experimental with one group pretest-posttest design. The subjects in this study were all students of class XI MIA 3 SMAN 1 Wongsorejo for the academic year 2021-2022. The data collection technique used purposive sampling technique. The instruments used are observation instruments and concept understanding tests. The results of the descriptive analysis show that the average value of students' conceptual understanding before the problem-based learning (PBL) model is applied is 34.59. Meanwhile, the average value of students' conceptual understanding after applying the problem based learning (PBL) model is 76.62.